Lemma 13.4.8. Let $\mathcal{D}$ be a pre-triangulated category. Let

$(a, b, c) : (X, Y, Z, f, g, h) \to (X', Y', Z', f', g', h')$

be a morphism of distinguished triangles. If one of the following conditions holds

1. $\mathop{\mathrm{Hom}}\nolimits (Y, X') = 0$,

2. $\mathop{\mathrm{Hom}}\nolimits (Z, Y') = 0$,

3. $\mathop{\mathrm{Hom}}\nolimits (X, X') = \mathop{\mathrm{Hom}}\nolimits (Z, X') = 0$,

4. $\mathop{\mathrm{Hom}}\nolimits (Z, X') = \mathop{\mathrm{Hom}}\nolimits (Z, Z') = 0$, or

5. $\mathop{\mathrm{Hom}}\nolimits (X, Z') = \mathop{\mathrm{Hom}}\nolimits (Z, X') = 0$

then $b$ is the unique morphism from $Y \to Y'$ such that $(a, b, c)$ is a morphism of triangles.

Proof. If we have a second morphism of triangles $(a, b', c)$ then $(0, b - b', 0)$ is a morphism of triangles. Hence we have to show: the only morphism $b : Y \to Y'$ such that $X \to Y \to Y'$ and $Y \to Y' \to Z'$ are zero is $0$. We will use Lemma 13.4.2 without further mention. In particular, condition (3) implies (1). Given condition (1) if the composition $g' \circ b : Y \to Y' \to Z'$ is zero, then $b$ lifts to a morphism $Y \to X'$ which has to be zero. This proves (1).

The proof of (2) and (4) are dual to this argument.

Assume (5). Consider the diagram

$\xymatrix{ X \ar[r]_ f \ar[d]^0 & Y \ar[r]_ g \ar[d]^ b & Z \ar[r]_ h \ar[d]^0 \ar@{..>}[ld]^\epsilon & X \ar[d]^0 \\ X' \ar[r]^{f'} & Y' \ar[r]^{g'} & Z' \ar[r]^{h'} & X' }$

We may choose $\epsilon$ such that $b = \epsilon \circ g$. Then $g' \circ \epsilon \circ g = 0$ which implies that $g' \circ \epsilon = \delta \circ h$ for some $\delta \in \mathop{\mathrm{Hom}}\nolimits (X, Z')$. Since $\mathop{\mathrm{Hom}}\nolimits (X, Z') = 0$ we conclude that $g' \circ \epsilon = 0$. Hence $\epsilon = f' \circ \gamma$ for some $\gamma \in \mathop{\mathrm{Hom}}\nolimits (Z, X')$. Since $\mathop{\mathrm{Hom}}\nolimits (Z, X') = 0$ we conclude that $\epsilon = 0$ and hence $b = 0$ as desired. $\square$

Comment #5898 by Taro konno on

Two typos in the proof ; $b : Y \to Y' \to Z'$ should be $g' \circ b : Y \to Y' \to Z'$ in "Given condition (1) if the composition $b:Y \to Y′ \to Z′$ is zero, then $b$ lifts to a morphism $Y \to X′$ which has to be zero." $b = g \circ \epsilon$ should be $b = \epsilon \circ g$ in "We may choose $\epsilon$ such that $b = g \circ \epsilon$. "

There are also:

• 13 comment(s) on Section 13.4: Elementary results on triangulated categories

In your comment you can use Markdown and LaTeX style mathematics (enclose it like $\pi$). A preview option is available if you wish to see how it works out (just click on the eye in the toolbar).